Optimization and characterization of a flow cell for heat‐transfer‐based biosensing. Issue 9 (20th February 2017) - Stilman, Wouter; Jooken, Stijn; Wackers, Gideon; Cornelis, Peter; Khorshid, Mehran; Yongabi, Derick; Akkermans, Onno; Dyson, Simba; van Grinsven, Bart; Cleij, Thomas; van Ijzendoorn, Leo; Wagner, Patrick; et al.
Abstract : In this article, we report on the development of a flow cell optimized for the heat‐transfer method, a versatile biosensing technique. The design of the flow cell ensures that the heat flow is focused with minimal heat loss through the surroundings of the cell. This results in a more stable measuring signal and an improved sensitivity of the measuring technique. The sensor was characterized by performing background measurements in air, water, and phosphate buffered saline (PBS) solution. Heat flow through the setup was simulated using COMSOL in order to provide insight in the contribution of convection to the heat flow and recommendations for possible future improvements to the cell. Additionally, a two‐step algorithm for calculating thermal resistance was defined, allowing the user to accurately derive thermal conductivity from experimental data. Finally, the potential of the flow cell for bacteria ( Escherichia coli ) detection was assessed and compared with the results obtained in the original HTM setup in a similar experiment. This experiment demonstrates that we were able to improve the limit‐of‐detection (LoD) to 2.10 × 10 4 colony forming units (CFU) mL −1 by changing the geometry of the measuring cell. Sensor setup for thermal biodetection experiments a directed heat flow.